Impact of radiation and heat generation/absorption in a Walters' B fluid through a porous medium with thermal and thermo diffusion in the presence of chemical reaction. (4th March 2023) - B. Johnson, Akinbo; B. I, Olajuwon
ABSTRACT: In this paper, the analytical technique is adopted to investigate the behaviours of the various patients in the non-Newtonian type model of a Walters' B fluid through a porous medium with the interactive impact of thermal radiation, heat generation/absorption and diffusion thermo impact in the presence of thermal diffusion and chemical reaction. The highly nonlinear systems of equations responsible for the behaviours of the model are modified to the system of coupled nonlinear ordinary differential equations via the fluid variables. The converted equations are executed by Homotopy Analysis Method (HAM). The significance of magnetic parameter, local Weissenberg number as well as other parameters encountered are discussed accordingly. Among the major finding is the variation in thermal buoyancy parameter, which accelerates the motion of the fluid and cools the problem with a significant role of cooling of the system and other electronic panels in the science-related field while the quiescent-fluid gained thermal-effect on the account of the penetration of strong convective-heating for different values of convective-heat parameter which contributes to the drying of material components in technological-related disciplines.